1987
DOI: 10.1086/165165
|View full text |Cite
|
Sign up to set email alerts
|

Molecular abundances in OMC-1 - The chemical composition of interstellar molecular clouds and the influence of massive star formation

Abstract: We present here an investigation of the chemical composition of the various regions in the core of the Orion molecular cloud (OMC-1) based on results from the Caltech Owens Valley Radio Observatory (OVRO) millimeter-wave spectral line survey (Sutton et al.; Blake et al.). This survey covered a 55 GHz interval in the 1.3 rom (230 GHz) atmospheric window and contained emission from over 800 resolved spectral features. Of the 29 identified species 14 have a sufficient number of detected transitions to be investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

71
732
5
3

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 876 publications
(811 citation statements)
references
References 35 publications
71
732
5
3
Order By: Relevance
“…Millimeter and submillimeter single-dish surveys show thousands of lines of nearly a hundred different molecules (e.g., Blake et al 1987;Sutton et al 1995;Schilke et al 1997Schilke et al , 2001), whereas interferometer studies reveal intriguing chemical differentiation over scales of less than 2000 AU (e.g., Wright et al 1996;Blake et al 1996). In spite of this wealth of data, molecules such as CO 2 and C 2 H 2 , which are symmetric and thus lack a dipole moment, cannot be observed through rotational transitions at millimeter Send offprint requests to: A. M. S. Boonman, e-mail: boonman@strw.leidenuniv.nl Based on observations with ISO, an ESA project with instruments funded by ESA Member States (especially the PI countries: France, Germany, The Netherlands and the UK) and with the participation of ISAS and NASA. wavelengths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Millimeter and submillimeter single-dish surveys show thousands of lines of nearly a hundred different molecules (e.g., Blake et al 1987;Sutton et al 1995;Schilke et al 1997Schilke et al , 2001), whereas interferometer studies reveal intriguing chemical differentiation over scales of less than 2000 AU (e.g., Wright et al 1996;Blake et al 1996). In spite of this wealth of data, molecules such as CO 2 and C 2 H 2 , which are symmetric and thus lack a dipole moment, cannot be observed through rotational transitions at millimeter Send offprint requests to: A. M. S. Boonman, e-mail: boonman@strw.leidenuniv.nl Based on observations with ISO, an ESA project with instruments funded by ESA Member States (especially the PI countries: France, Germany, The Netherlands and the UK) and with the participation of ISAS and NASA. wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the gas-phase CO 2 abundance is surprisingly low, ∼10 −7 , toward massive YSOs (van Dishoeck et al 1996;van Dishoeck 1998;Dartois et al 1998;Boonman et al 2000). Since the abundances of many gas-phase species are enhanced toward IRc2, in particular those of species involved in the gas-grain chemistry (e.g., Blake et al 1987;Charnley et al 1992), it is important to investigate whether the CO 2 chemistry follows this trend. Observations of C 2 H 2 and HCN are interesting because they are both significant in the carbon-and nitrogen chemistry, and because their excitation provides information on the physical conditions .…”
Section: Introductionmentioning
confidence: 99%
“…The best agreement with the observed line ratios and absolute intensities is found for a beam filling of 0.4. Positions 6 and 7 at the eastern MIR peak (Telesco & Gezari 1992) (Blake et al 1987) and were suggested by chemical models (Farquhar et al 1994). …”
Section: Radiative Transfer Calculationsmentioning
confidence: 90%
“…Observationally, hot cores are characterized by high abundances of fully hydrogenated molecules such as NH 3 , H 2 S, and H 2 O (e.g., Gensheimer et al 1996), as well as saturated complex organic molecules like CH 3 OH, CH 3 CN, CH 3 OCH 3 and HCOOCH 3 (e.g., Hatchell et al 1998). Examples of hot cores include the Orion hot core and compact ridge (e.g., Blake et al 1987, Sutton et al 1995, SgrB2(N) (e.g., Kuan & Snyder 1996), W 3(H 2 O) (e.g., and objects near ultracompact H II regions such as G34.3+0.15 (Macdonald et al 1996; see chapter by Churchwell). The observed abundances of the species can vary significantly from region to region.…”
Section: Hot Core Regionsmentioning
confidence: 99%